“Determinación de la viabilidad de semilla de sacha inchi (plukenetia volubilis) bajo condiciones de almacenamiento en cámara fría y condiciones normales” en tarapoto” - Vargas Lápiz, Gilver (2009)
The present research work aimed to determine the viability of the seed des Sacha inchi under dos (in normal conditions and cold) storage conditions for a period of five months. This work was conducted on the premises of the Regional Committee of seeds of San Martin this located in the province of San Martin to a South latitude 6 ° 30'00 ", length West 76 ° 29'00" at an altitude of 330 m.s.n.m.m. Is apply a DCR with arrangement factorial 2 by 6, with four replications per treatment. The seeds of inchi sacha Pinto recodo accession was collected from the District of Lamas (Pinto Recodo). In addition the CORESE-SM facilitated work, through its facilities, likewise INRA provided the facilities of your cold room where the seeds were stored. In the obtained analysis reported higher averages of germination (normal seedlings) were the second and third month of storage in the two conditions (cold and conditions...)